2015
DOI: 10.1002/jbmr.2688
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Specialist-Led, School Physical Education Program on Bone Mass, Structure, and Strength in Primary School Children: A 4-Year Cluster Randomized Controlled Trial

Abstract: This 4-year cluster randomized controlled trial of 365 boys and 362 girls (mean age 8.1 AE 0.3 years) from grade 2 in 29 primary schools investigated the effects of a specialist-taught physical education (PE) program on bone strength and body composition. All children received 150 min/week of common practice (CP) PE from general classroom teachers but in 13 schools 100 min/week of CP PE was replaced by specialized-led PE (SPE) by teachers who emphasized more vigorous exercise/games combined with static and dyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
69
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(71 citation statements)
references
References 37 publications
1
69
1
Order By: Relevance
“…Researchers have found that an adolescent's response to strength training optimal during SMR 4 and 5 in both male and female athletes (2,4,6,19,20). Some research has additionally shown that high intensity exercise in primary school children enhances musculoskeletal and metabolic outcomes in pre-and early-pubertal girls (21).…”
Section: Muscle Growth and Strengthmentioning
confidence: 99%
“…Researchers have found that an adolescent's response to strength training optimal during SMR 4 and 5 in both male and female athletes (2,4,6,19,20). Some research has additionally shown that high intensity exercise in primary school children enhances musculoskeletal and metabolic outcomes in pre-and early-pubertal girls (21).…”
Section: Muscle Growth and Strengthmentioning
confidence: 99%
“…However, this is still one of the best intervention strategies for the young population in general. Besides having applicability, it demonstrates relevant results in bone health 26 .…”
Section: Discussionmentioning
confidence: 96%
“…In addition, and reinforcing the role of physical activity, a randomized control trial study in obese children showed higher increase in bone mineral content in trained group compared to the diet-alone 24 . Further, increased bone mass during childhood and adolescence (obese or non-obese) has been associated to the frequency, intensity and type of physical activity 25 , especially in Physical Education 26 .…”
Section: Discussionmentioning
confidence: 99%
“…In fact, additional school-based physical education conducted over seven years was associated with greater tibial structure, strength, and region-specific adaptations in cortical bone mass and density distribution in girls, but not in boys [ 79 ]. This data was confirmed by a 4-year cluster randomized controlled trial involving 365 boys and 362 girls aged 8.1 ± 0.3 years, evaluating the effects of a specialist-taught physical education (PE) program on bone strength and body composition [ 80 ]. These last group, in comparison to other children receiving PE from general classroom teachers, showed similar gains in total body BMC, FM, and muscleCSA in both sexes, but a greater gain in total body LM, cortical area (CoA) and CoTh at the mid-tibia and mid-radius in girls [ 80 ].…”
Section: Introductionmentioning
confidence: 91%
“…This data was confirmed by a 4-year cluster randomized controlled trial involving 365 boys and 362 girls aged 8.1 ± 0.3 years, evaluating the effects of a specialist-taught physical education (PE) program on bone strength and body composition [ 80 ]. These last group, in comparison to other children receiving PE from general classroom teachers, showed similar gains in total body BMC, FM, and muscleCSA in both sexes, but a greater gain in total body LM, cortical area (CoA) and CoTh at the mid-tibia and mid-radius in girls [ 80 ]. In a cross-sectional study involving 724 adolescents using objective measures of physical activity, the highest impact levels of physical activity were positively associated with the periosteal bone mineral accrual at the femoral neck and other hip sites [ 81 ].…”
Section: Introductionmentioning
confidence: 91%